Improvement of the method of semiotic analysis of materials for detection of informational-psychological impact - Trofymchuk, Oleksandr; Zabolotnyi, Serhyi; Katsalap, Vitaliy (Kyiv National University of Construction and Architecture, 2025)
The improvement of the method of semiotic analysis is carried out in the interests of identifying the informational and psychological impact on target audiences. This is due to the fact that there is a discrepancy in the way of determining the dominant messages in the information space. The main narratives used to justify armed aggression, in particular the theorization of the “SVO”, are characterized, demonization of Ukraine and the West, as well as the creation of the image of Russia as a victim of an international conspiracy. The essence of the integration of textual and visual elements in propaganda materials to form an emotional informational and psychological impact on young people, who are the main target audience, is explained.The purpose of the article is to improve the method of semiotic analysis to identify informational and psychological impact by taking into account the hypothesis of information management, which will allow to increase the capabilities of the Ukrainian defense forces in countering information threats in the deoccupied territories of Ukraine.The conducted research allowed us to outline the main areas of work in the information space in the deoccupied territories of Ukraine and develop information technology to effectively counter Russian propaganda. During a comprehensive analysis of methods of informational and psychological influence on specific target audiences, the content of narrative elements that determine their behavior was obtained. New approaches to the use of informational and psychological operations tools were analyzed, which allows for a deeper understanding of their role in manipulating public consciousness and ensuring ideological influence in the long term. The result of the study is a description and decomposition of the method of semiotic analysis for identifying informational and psychological influence on specific target audiences with a step-by-step analysis of specific manipulations. This expands the theoretical understanding of the use of materials as tools of informational and psychological influence, contributing to a deeper analysis of Russia's propaganda strategies in the education system.